Answer:
The output of the function y = -6x + 8 when the input is x = 20 is -112.
Step-by-step explanation:
y = -6x + 8
Input the value x = 20.
y = -6(20) + 8
Multiply -6 and 20.
y = -120 + 8
Add -120 and 8.
y = -112.
Answer:
i didn't learn algebra or geometry or spatial sense when i was in sixth grade
Step-by-step explanation:
$123.75 you would round all of them to the nearest hundreth
Answer:
1.03703703704
Step-by-step explanation:
i d k if this is what ur looking for but hope this helped :)
<h2>
Explanation:</h2>
We use an equation to say that two things are equal. An equation always has an equal sign "=". So an equation tells us that the left side is equal to the right side. In this case, we have the following equation:
![a =5](https://tex.z-dn.net/?f=a%20%3D5)
So the only value that makes this equation to be true is 5, because:
![5=5](https://tex.z-dn.net/?f=5%3D5)
For instance, let's choose another value, say, 8. So substituting:
![6 =5 \ \text{So this statement is false because} \ 6\neq 5](https://tex.z-dn.net/?f=6%20%3D5%20%5C%20%5Ctext%7BSo%20this%20statement%20is%20false%20because%7D%20%5C%206%5Cneq%205)